Does Trade Credit Substitute Bank Credit? : Evidence From Firm-Level Data - De Blasio, Guido (Washington, D.C. : International Monetary Fund, 2003)
The paper examines micro data on Italian manufacturing firms' inventory behavior to test the Meltzer (1960) hypothesis according to which firms substitute trade credit for bank credit during periods of monetary tightening. It finds that their inventory investment is constrained by the availability of trade credit. As for the magnitude of the substitution effect, however, this study finds that it is not sizable. This is in line with the micro theories of trade credit and the evidence on actual firm practices, according to which credit terms display modest variations over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet